MONITORING EPIZOOTIC SITUATION OF DOG TRICHURIASIS ON THE TERRITORY OF UKRAINE - Dolhin, O. S. (Scientific Progress & Innovations, 2021)
At present, the problem of dog parasitic diseases caused by helminthes is becoming more and more topical among animals’ owners in Ukraine. It is also stipulated by the fact that a considerable part of pathogens causing dog parasitic diseases are zoo-anthroponoses, that is they can infest humans as well. Dog trichuriasis caused by nematodes of Trichuris Roederer, 1761 (Adenophorea, Trichuridae) genus is one of such diseases. Generally, trichuratoses’ causative agents are referred to the most spread nematodes in different geographical and climatic regions of our planet. In this connection, studying the epizootic situation concerning trichuriasis invasion of dogs on the territory of Ukraine is a topical direction for researches. The investigations of spreading trichuriasis among the population of domestic dogs in our country was conducted based on the results of analyzing the statistical data of reporting documentation of the State Scientific and Research Institute in Laboratory Diagnostics and Veterinary-Sanitary Expert Examination (the city of Kyiv) during 2016–2020. It has been established that helminthic infestations of dogs are considerably spread on the territory of Ukraine where the average prevalence of infection makes 4.43 % varying from 2.8 to 5.7 %. It has been registered that the percentage of helminthoses among the detected dog parasitic diseases makes 33 %. At conducting monitoring studies as to spreading dog helminthoses on the territory of this country during the period of 2016–2020, it has been fixed the share of dog trichuriasis among the detected helminthoses was 6.3 %. Within the investigated period, the ratio of trichuriasis infestation varied from 7.4 to 8.7 % among other dog helminthoses. According to the data of the reporting documentation, it has been registered that in 2020 there was a sharp decrease to 1.7 % of detected dog trichuriasis cases. While studying dog trichuriasis prevalence on the territory of Ukraine, the tendency to gradual increase of this indicator from 11.8 % in 2016 to 50.0 % in 2020 was registered. The obtained data have theoretical and practical value both for veterinary doctors and animal owners. The conducted analysis enables to supplement the existing data concerning the spreading of this infection in Ukraine; it also gives the corresponding directions as to further researches for developing effective, scientifically grounded schemes of treatment and prevention measures.